Die for you - Unger, Lisa, 1970- (Shaye Areheart Books, 2009)
When successful novelist Isabel Raines learns that everyone that her husband worked with is dead--and that her missing husband has been legally dead for some time--she will not rest until she finds the truth about him. Who he was, where he's gone, and how he was able to deceive her so completely.